2012
DOI: 10.1097/nnd.0b013e318272584a
|View full text |Cite
|
Sign up to set email alerts
|

Retention of New Graduate Nurses

Abstract: The authors examine the literature on resiliency and relate important concepts to the retention of new graduate nurses. Changes in the support of new graduates are proposed as a means to increase retention in the nursing profession. Developing resilient graduate nurses who can withstand the pressures of the workplace is at the center of retention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
0
0
1
Order By: Relevance
“…It is not surprising that experienced colleagues treat novice nurses irrationally (Maria et al, 2020). So it is essential to support novice nurses in their new workplace, previous studies showed that the majority of novice nurses had insufficient supporting resources, which increased errors, conflicts, staff tensions, ineffective patient care, and reduced productivity (Moran, 2012; Tastan et al, 2013; Theisen & Sandau, 2013). It has been well established that a supporting and encouraging workplaces could enhance the creativity and organizational commitment of novice nurses (Tastan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising that experienced colleagues treat novice nurses irrationally (Maria et al, 2020). So it is essential to support novice nurses in their new workplace, previous studies showed that the majority of novice nurses had insufficient supporting resources, which increased errors, conflicts, staff tensions, ineffective patient care, and reduced productivity (Moran, 2012; Tastan et al, 2013; Theisen & Sandau, 2013). It has been well established that a supporting and encouraging workplaces could enhance the creativity and organizational commitment of novice nurses (Tastan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Essa condição de pressão pode levar a exaustão física e emocional, que se retrata, principalmente, na saúde mental do profissional docente que apresenta índices elevados de estresse, instalando um ciclo em que atividades docentes associadas aos fatores estressores sociais cotidianos os levam a apatia, conformação e acomodação, que resulta em insatisfação e frustração (5,6) .…”
Section: Introductionunclassified